Echo time-dependent observed Lung T1 in patients with chronic obstructive pulmonary disease in correlation with quantitative imaging and clinical indices - Triphan, Simon M. F.; Weinheimer, Oliver; Gutberlet, Marcel; Heußel, Claus Peter; Vogel-Claussen, Jens; Herth, Felix; Vogelmeier, Claus F.; Jörres, Rudolf A.; Kauczor, Hans-Ulrich; Wielpütz, Mark Oliver; Biederer, Jürgen; Jobst, Bertram (Journal of magnetic resonance imaging, 2021)
Background There is a clinical need for imaging-derived biomarkers for the management of chronic obstructive pulmonary disease (COPD). Observed pulmonary T1 (T1(TE)) depends on the echo-time (TE) and reflects regional pulmonary function. Purpose To investigate the potential diagnostic value of T1(TE) for the assessment of lung disease in COPD patients by determining correlations with clinical parameters and quantitative CT. Study Type Prospective non-randomized diagnostic study. Population Thirty COPD patients (67.7 ± 6.6 years). Data from a previous study (15 healthy volunteers [26.2 ± 3.9 years) were used as reference. Field Strength/Sequence Study participants were examined at 1.5 T using dynamic contrast-enhanced three-dimensional gradient echo keyhole perfusion sequence and a multi-echo inversion recovery two-dimensional UTE (ultra-short TE) sequence for T1(TE) mapping at TE1-5 = 70 μsec, 500 μsec, 1200 μsec, 1650 μsec, and 2300 μsec. Assessment Perfusion images were scored by three radiologists. T1(TE) was automatically quantified. Computed tomography (CT) images were quantified in software (qCT). Clinical parameters including pulmonary function testing were also acquired. Statistical Tests Spearman rank correlation coefficients (ρ) were calculated between T1(TE) and perfusion scores, clinical parameters and qCT. A P-value <0.05 was considered statistically significant. Results Median values were T1(TE1-5) = 644 ± 78 msec, 835 ± 92 msec, 835 ± 87 msec, 831 ± 131 msec, 893 ± 220 msec, all significantly shorter than previously reported in healthy subjects. A significant increase of T1 was observed from TE1 to TE2, with no changes from TE2 to TE3 (P = 0.48), TE3 to TE4 (P = 0.94) or TE4 to TE5 (P = 0.02) which demonstrates an increase at shorter TEs than in healthy subjects. Moderate to strong Spearman's correlations between T1 and parameters including the predicted diffusing capacity for carbon monoxide (DLCO, ρ < 0.70), mean lung density (MLD, ρ < 0.72) and the perfusion score (ρ > −0.69) were found. Overall, correlations were strongest at TE2, weaker at TE1 and rarely significant at TE4-TE5. Data Conclusion In COPD patients, the increase of T1(TE) with TE occurred at shorter TEs than previously found in healthy subjects. Together with the lack of correlation between T1 and clinical parameters of disease at longer TEs, this suggests that T1(TE) quantification in COPD patients requires shorter TEs. The TE-dependence of correlations implies that T1(TE) mapping might be developed further to provide diagnostic information beyond T1 at a single TE. Level of Evidence 2 Technical Efficacy Stage 1